Diplosmittia caribensis, a new Orthocladiinae (Diptera: Chironomidae) from the Dominican Republic - Wiedenbrug, Sofia; Silva, Fabio Laurindo Da (Zootaxa, 2016)
The genus Diplosmittia was erected by Sæther (1981) based on Diplosmittia harrisoni from St. Lucia and St. Vincent in the British West Indies. Prior to the present study the genus comprised nine species, all except D. carinata Sæther were known only from Neotropical Region (Ashe & O’Connor, 2012). During sampling in the surroundings of a highly organic polluted river, in the National Botanical Garden in Santo Domingo, Dominican Republic, the present second author collected several imagines of Diplosmittia that did not fit any taxon treated in the recent review of the genus (Pinho et al. 2009). In the present paper, the male of this new species is described and illustrated.